PENINGKATAN KEAKTIFAN SISWA KELAS V SD INPRES 4/82 WAJI DALAM PEMBELAJARAN IPA MELALUI PENERAPAN MODEL PEMBELAJARAN TREASURE HUNT - Sudarto, Sudarto; Asriadi, Asriadi; Risma Febriani Syam (Bajang Institute, 2024)
This research is a classroom action research which aims to find out whether the Treasure Hunt learning model can or cannot increase the activity of the 5th grade students at SD Inpres 4/82 Waji in learning of science. The subjects of this research were of the 5th grade students at SD Inpres 4/82 Waji in totally of 15 students. The data collection techniques used were observation and documentation techniques and the data analysis techniques were of quantitative descriptive techniques. Research results: In Cycle I there were of 40% of the number of students who were active, while 60% of the number of students were inactive and in the Cycle II there were 80% of the number of students who were active, while 20% of the number of students appeared to be inactive. Conclusion: The application of the Treasure Hunt learning model can increase the activeness of the 5th grade students at SD Inpres 4/82 Waji, Tellu Siattinge District in their science learning